OVERREACTION ANALYSIS OF WINNER AND LOSSER SHARE ON THE INDONESIA STOCK EXCHANGE (CASE STUDY OF LQ-45 INDEX 2016-2019 PERIOD) - Febriani, Aulia Putri (Program Pascasarjana, Universitas Riau, 2023)
This study, conducted with a robust and transparent methodology, aims to determine the occurrence of market overreaction on the Indonesian stock exchange. We analyze two distinct periods, semiannual and annual, from 2016 to 2019, focusing on the LQ-45 index. Our methodology involves classifying stocks into two portfolios based on the Cumulative Abnormal Return (CAR) value. The winner portfolio represents one-third of the stocks with the highest CAR value, while the loser portfolio represents one-third with the lowest CAR value. The presence of overreaction is indicated when the loser's portfolio outperforms the winner's. Our findings from this rigorous methodology, which we detail in the paper, reveal a clear and novel phenomenon of market overreaction on the Indonesian Stock Exchange, particularly on stocks included in the LQ-45 index, but notably, only in the semi-annual period. There is no evidence of market overreaction for the annual period, suggesting a nuanced market behavior that warrants further investigation.